Discriminative validity of a lower extremity inertial sensor setup to quantify biomechanical load during a standardized soccer training drill - Bastiaansen, B. J. C.; Vegter, R. J. K.; Lemmink, K. A. P. M.; Brink, M. S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Training load quantification could support planning future training and thereby improve player performance. However, current monitoring systems do not monitor lower extremity biomechanical load and thus important information might be neglected. This explorative study assessed the discriminative validity of a new inertial sensor setup [1] to quantify lower extremity biomechanical load during a standardized soccer training drill.